2011
DOI: 10.3390/molecules16043444
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Compounds from Propolis Collected in Anhui, China

Abstract: The antioxidant activities of the chloroform, ethyl acetate and n-butanol extract fractions from propolis collected in Anhui, China were evaluated in this study. The ethyl acetate fraction contained the highest amount of total phenolics and total flavonoids, and showed the greatest 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical scavenging capacities and Ferric Reducing/Antioxidant Power (FRAP). The antioxidant activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 31 publications
8
127
0
6
Order By: Relevance
“…In our study TPC of EEP was measured at 124.6 ± 1.5 mg GAE/g sample dry weight using the FolinCiocalteu method. TPC in ethanolic extracts of propolis have been reported at 174.7 mg GAE/g sample dry weight from China [25], 151.5 mg GAE/g sample dry weight from Brazil [1] and 31.2 -299 mg GAE/g sample dry weight from other parts of the world [24]. TFC of EEP in this study was 42 ± 0.8 QE/g sample dry weight.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In our study TPC of EEP was measured at 124.6 ± 1.5 mg GAE/g sample dry weight using the FolinCiocalteu method. TPC in ethanolic extracts of propolis have been reported at 174.7 mg GAE/g sample dry weight from China [25], 151.5 mg GAE/g sample dry weight from Brazil [1] and 31.2 -299 mg GAE/g sample dry weight from other parts of the world [24]. TFC of EEP in this study was 42 ± 0.8 QE/g sample dry weight.…”
Section: Discussionmentioning
confidence: 46%
“…TFC of EEP in this study was 42 ± 0.8 QE/g sample dry weight. TFC in ethanolic extracts of propolis of 45.1 mg QE/g sample dry weight have been reported from China [25] and 2.5 -176 mg QE/g sample dry weight from other parts of the world [24]. The FRAP method was used to determine total antioxidant capacities of a compound.…”
Section: Discussionmentioning
confidence: 99%
“…TPC values of these samples was between 10.94 and 79.23 mg GAE/g propolis. 30 TPC and TFC values of propolis extracts have been reported that as 174.7 mg GAE/g dry sample, 45.1 mg QE/g dry sample from China, 31 between 150-197 mg GAE/g dry sample, 35.64-62.04 mg QE/g dry sample from Poland, 32 and 31.2-299 mg GAE/g dry sample, 2.5-176 mg QE/g dry sample from other parts of the world, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…More than 300 substances have been identified in samples of propolis from different regions (PEREIRA et al, 2002). Classes of compounds commonly found in propolis include flavonoids (PETROVA et al, 2010), prenylated flavanones (EL-BASSUONY, 2009), benzopyranes (SILICI et al, 2007), benzophenones (ISHIDA et al, 2011), caffeic acid esters (CAO et al, 2011), triterpenoids (PEREZ et al, 2009), benzoic acid (XU et al, 2010) and cin na mi c aci d deri va ti ves (YANG, 2011), an d naphthoquinone epoxides (TRUSHEVA et al, 2006).…”
Section: Introductionmentioning
confidence: 99%